Peripartum Cardiomyopathy and Spouses' Experiences of Persistent Uncertainty. Issue 4 (July 2022) - Hess, Rosanna F.; Donnenwirth, Jo Ann
Abstract: Purpose: The purpose of this study was to explore the experiences of spouses whose wives had peripartum cardiomyopathy (PPCM). Design & Methods: Participants were recruited for this phenomenological study through online sites Facebook and SavetheMommies. Fifteen men from four countries participated through semistructured phone interviews conducted between October 2019 and August 2020. Data were analyzed using a modified version of the constant comparison method. Results: The overarching theme of spouses' experiences was Living with the 'what ifs' of persistent uncertainty . Four main themes were: Feeling the shock, Facing the challenge, Figuring out a new normal, and Finding meaning . Spouses had to deal with the fear of their wives' heart failure relapse or death, changed marital and parental roles, and unclear expectations of the future. Clinical Implications: PPCM is a rare complication of pregnancy with uncertain implications for the future that can have a profound impact on the woman's spouse and family. Our findings should alert nurses and other health care professionals to the need for emotional, spiritual, and informational support of spouses or partners of women who have PPCM. Nurses should include spouses and partners in care and communication to make sure they are as informed as possible, have their questions and concerns addressed as needed, and receive adequate follow-up support. Abstract : Peripartum cardiomyopathy is a serious complication of pregnancy, affecting approximately 1 in 1000 women in the United States. In this study, spouses of women who were diagnosed with peripartum cardiomyopathy were interviewed. Participants described their experiences and the ongoing uncertainty of the future health of their wives. These data can help to guide care for spouses of women with pregnancy complications.